Green Synthesis and Modification of RuO2 Materials for the Oxygen Evolution Reaction - Devadas, Abirami; Baranton, Stève; Coutanceau, Christophe (Frontiers in Energy Research, 2020)
Ion exchange method as a green synthesis route is proposed to prepare hydrous ruthenium oxide nanoparticles (H-RuO2). Calcination of H-RuO2 at 350°C resulted in the crystalline rutile RuO2 nanoparticles (C-RuO2). Treatment of H-RuO2 with 20 vol% ammonium hydroxide solution under microwave irradiation and calcination at 350°C resulted in a highly electrocatalytic active crystalline RuO2 nanoparticles (A-C-RuO2). Electrocatalytic performances of H-RuO2, C-RuO2 and A-C-RuO2 for the oxygen evolution reaction in 0.50 mol L−1 H2SO4 medium are evaluated and compared. Improved performances towards the oxygen evolution reaction are observed for A-C-RuO2 when compared to C-RuO2. Based on XRD, TEM, XPS and Raman characterizations performed on all the specimens, it is deduced that the physicochemical properties (crystallinity, mean crystallite size, level of hydrous rutile content) are varied for A-C-RuO2 when compared to C-RuO2. Structure-property correlation has been established to describe the higher electrocatalytic activity of A-C-RuO2.